Erianin inhibits human lung cancer cell growth via PI3K/Akt/mTOR pathway in vitro and in vivo - Zhang, Hui‐qiong; Xie, Xiao‐fang; Li, Gang‐min; Chen, Jun‐ren; Li, Meng‐ting; Xu, Xin; Xiong, Qiu‐yun; Chen, Guan‐ru; Yin, Yan‐peng; Peng, Fu; Chen, Yan; Peng, Cheng (Phytotherapy research, 2021)
Erianin is a small‐molecule compound that is isolated from Dendrobium chrysotoxum Lindl. In recent years, it has been found to have evident antitumor activity in various cancers, such as bladder cancer, cervical cancer, and nasopharyngeal carcinoma. In this study, we assessed the effect of erianin on lung cancer in terms of cell growth inhibition and the related mechanism. First, erianin at a concentration of less than 1 nmol/L exhibited cytotoxicity in H1975, A549, LLC lung cancer cells, did not cause marked growth inhibition in normal lung and kidney cells, induced obvious apoptosis and G2/M phase arrest of cells, and inhibited the migration and invasion of lung cancer cells in vitro. Second, in a mouse xenograft model of lewis lung cancer (LLC), oral administration of erianin (50, 35, and 10 mg kg−1 day−1 for 12 days) substantially inhibited nodule growth, reduced the fluorescence counts of lewis cells and the percentage vascularity of tumor tissues, increased the number of apoptotic tumor cells, the thymus indices, up‐regulated the levels of interleukin (IL)‐2 and tumor necrosis factor‐α (TNF‐α), decreased IL‐10 levels and the spleen index, and enhanced immune function. Lastly, the possible targets of erianin were determined by molecular docking and verified via western blot assay. The results indicated that erianin may achieve the above effects via inhibiting the phosphoinositide 3‐kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) pathway in vitro and vivo. Taken together, the results showed that erianin had obvious antitumor effects via inhibiting the PI3K/Akt/mTOR pathway in vitro and vivo and may have potential clinical value for the treatment of lung cancer.